Optimization of Supplier Selection and Order Size Determination in Multi-Item and Multi-Period Packaging Procurement - NURUL QOLBI EL AZIZAH; Rika Ampuh Hadiguna; Elita Amrina (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This research aims to develop an optimization model that systematically integrates key factors such as price, supplier capacity, Minimum order quantity (MOQ), and ordering costs into a single decision framework. The model was developed using the Capacitated Allocation Supplier Model (CASM) based on Mixed Integer Linear Programming (MILP) with a 12-period horizon (January–December 2025). The objective is to determine the optimal combination of supplier selection and order quantity allocation that minimizes total procurement costs while ensuring supply continuity. The results indicate that the CASM–MILP model successfully reduces total procurement costs from IDR 1.671.889.794,10 to IDR 1.350.088.510, yielding IDR 321.801.284,10, or 19,25% savings. Although the percentage appears modest, the savings are significant since they are achieved without disrupting production schedules or packaging availability. Moreover, the proposed model enhances transparency and rationality in decision-making and lays the foundation for future data-driven procurement systems. Overall, this research demonstrates that the MILP-based optimization approach effectively improves cost efficiency in multi-item and multi-period procurement systems, offering practical contributions for industry management and theoretical insights for operations management studies. Contribution to Sustainable Development Goals (SDGs):SDG 9 – Industry, Innovation and InfrastructureSDG 11– Sustainable Cities and CommunitiesSDG 8 – Decent Work and Economic Growth